PENGARUH MODEL PEMBELAJARAN PBL BERBASIS TPACK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PEMBELAJARAN IPAS KELAS V SD - Merta Adelia, Cindy; Satianingsih, Rarasaning (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is an Influence of the TPACK-Based PBL Model on the Critical Thinking Skills of Students in Science Learning Class V at SDN Dukuh Menanggal 1/424 Surabaya. The background of this study is the low critical thinking skills of students and the use of inappropriate learning models in the learning process. This study is a quantitative study using the Quasi Experiment method with the Post-Test Only Nonequivalent Control Group Design. The population in this study were 60 students in class V of SDN Dukuh Menanggal 1/424 Surabaya. The sample of this study used class VA with 29 students and class VB with 31 students. The data collection technique used in this study was through tests. The data analysis technique used the normality test, homogeneity test, and t-test. The results of the study showed that there was an Influence of the TPACK-Based Problem Based Learning (PBL) Model on the Critical Thinking Skills of Students in Science Learning Class V of Elementary School. This is evidenced by the significant difference between the post-test results of the experimental group and the control group.